Location, non-agricultural employment, and vulnerability to poverty in rural Thailand - Lohmann, Carsten; Liefner, Ingo (ERDKUNDE, 2009)
The location of a household affects its vulnerability to poverty. For example, the opportunity to secure regional non-agricultural wage-employment (RNAwE) as a means of reducing vulnerability is distributed unevenly between periurban and rural-remote regions. Data from a recently completed survey of 2,200 rural households in northeastern Thailand, sponsored by the German Research Foundation (DFG), underline the importance of location as a factor in levels of poverty that are experienced: there are significant differences between peri-urban and rural-remote households regarding transport costs, travel times, participation in RNAwE, and total household income.